Role of Risk management practices on organisational performance - NAMUMBYA ANITAH (Uganda Christian university, 2024)
ABSTRACT Risk management plays a crucial role in enhancing organizational performance by identifying, assessing, and mitigating potential threats to business operations. This research explores the impact of risk management practices on organizational performance, focusing on key processes such as risk identification, risk assessment, and mitigation strategies. Through a review of existing literature and case studies, the study examines how effective risk management contributes to operational efficiency, financial stability, and competitive advantage. The research contributes to the existing body knowledge by providing empirical evidence on the role of risk management practices in achieving organizational performance. The findings reveal that organizations that implement comprehensive risk management frameworks are better equipped to navigate uncertainties, minimize losses, and optimize decision-making, ultimately driving sustainable performance. A mixed -method approach was employed, combining questionnaire of 36 respondents, findings and regression analysis. Findings indicates the strong positive correlation between risk management practices and organizational performance, with risk identification, assessment, and monitoring practices contributing to significantly improved performance. The study’s results suggest that organist ions can enhance their performance by implementing effective risk management practices, aligning with organizational goals and objectives. The findings have practical implications for organizations seeking to improve the their risk management practices and overall performances. This research highlights the importance of aligning risk management practices with strategic objectives to enhance resilience and long-term success (Hillson & Murray-Webster, 2017; ISO 31000:2018).